(untitled) (Economic and Political Thought, 2022)
The Plan for Health and Well-Being in the Western Balkans (2021–2025) is part of the development of the health care system, increasing its competitiveness and strengthening national and regional security of citizens by raising the level of medical security. This article presents and analyzes its assumptions, while providing a prelude to further in-depth research in this area.